A Comparison Study Between Original Fuzzy Petri Nets and the New Adapting Fuzzy Petri Nets Used in Power Systems Prognosis - خيربك طارق; احمد احمد; سليمان رهف (Latakia University Journal -Engineering Sciences Series, 2021)
The term prediction refers to means that anticipate potential hazards during electrical network operation before they occur in order to avoid their negative effects on operation and equipment. Petri fuzzy networks (FPNs) play an important role in this field due to their mathematical and topographic properties that allow the representation of a wide range of event probabilities. In this paper, we present a comparative study between conventional fuzzy Petri networks and AFPN-adapted fuzzy Petri networks, which we have developed in order to adapt to changing conditions affecting the network’s operation. We used the IEEE 9 bus system network to perform a comparison analysis at an overload condition and then as variable environmental conditions added and discussed the results.